2016
DOI: 10.4254/wjh.v8.i11.509
|View full text |Cite
|
Sign up to set email alerts
|

Extension for Community Health Outcomes-hepatitis C: Small steps carve big footprints in the allocation of scarce resources for hepatitis C virus treatment to remote developing areas

Abstract: Hepatitis C virus (HCV) infection is still a major health problem throughout the world. HCV patients living in rural areas are less fortunate than their counterparts residing in populous urbanized regions. The lack of medical resources and properly trained medical personnel in rural regions make it especially burdensome for HCV patients seeking treatment. Dr. Sanjeev Arora at the University of New Mexico Health Sciences Center took initiative to resolve the issue at hand by developing a model named Project Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Integrated hepatitis C care within drug use and psychiatric services delivered by a multidisciplinary team with case management services, with or without non‐invasive liver disease assessment, was associated with improved hepatitis C treatment uptake . Other strategies evaluated and shown to enhance hepatitis C linkage to care and treatment include dried blood spot testing, point‐of‐care hepatitis C testing, non‐invasive liver disease screening using transient elastography (FibroScan ® ) with facilitated referral to care, integrated hepatitis C care, patient navigation programmes, peer‐based support, financial incentive programmes and telemedicine . However, the majority of interventions that have been evaluated are specific for the interferon‐era.…”
Section: Interventions To Enhance Hepatitis C Prevention Testing Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated hepatitis C care within drug use and psychiatric services delivered by a multidisciplinary team with case management services, with or without non‐invasive liver disease assessment, was associated with improved hepatitis C treatment uptake . Other strategies evaluated and shown to enhance hepatitis C linkage to care and treatment include dried blood spot testing, point‐of‐care hepatitis C testing, non‐invasive liver disease screening using transient elastography (FibroScan ® ) with facilitated referral to care, integrated hepatitis C care, patient navigation programmes, peer‐based support, financial incentive programmes and telemedicine . However, the majority of interventions that have been evaluated are specific for the interferon‐era.…”
Section: Interventions To Enhance Hepatitis C Prevention Testing Andmentioning
confidence: 99%
“…39 Other strategies evaluated and shown to enhance hepatitis C linkage to care and treatment include dried blood spot testing, 55 64,65 peer-based support, [66][67][68][69][70][71][72][73][74][75][76][77] financial incentive programmes 78,79 and telemedicine. [80][81][82][83] However, the majority of interventions that have been evaluated are specific for the interferon-era.…”
Section: Linkage To Hepatitis C Care and Treatmentmentioning
confidence: 99%
“…Simplified HCV testing, including dried blood spot testing (McAllister et al, 2014) and point-of-care HCV testing (Bottero et al, 2015; Morano et al, 2014) has been shown to facilitate linkage to HCV care. Other strategies that have been demonstrated to facilitate linkage to HCV care and treatment include, non-invasive liver disease screening using transient elastography (FibroScan ® ) with facilitated referral to care (Foucher et al, 2009; Marshall et al, 2015; Moessner et al, 2011), integrated HCV care (Cullen et al, 2006; Evon et al, 2011; Ho et al, 2015; Knott et al, 2006; Masson et al, 2013; Zhou et al, 2016), patient navigation programs (Falade-Nwulia et al, 2016; Trooskin et al, 2015), and telemedicine (Arora et al, 2011; Lloyd et al, 2013; Mashru, Kirlew, Saginur, & Schreiber, 2017; Tahan, Almashhrawi, Kahveci, Mutrux, & Ibdah, 2016). …”
Section: Linkage To Hcv Care and Treatmentmentioning
confidence: 99%
“…These screening programs should be designed based on the current human resources in the public health system such as Behvarz and general practitioners (GPs). In addition, GPs can be trained for HCV therapy in targeted seminars and then they can be guided via telecommunication for more HCV therapy all over the country ( 86 ).…”
Section: Discussionmentioning
confidence: 99%